After they turn on the screen : use of information and communication technology in an upper secondary school in Iceland - Ásrún Matthíasdóttir 1956- (2015)
The main aim of is study is to seek to further the understanding of the influence of information and communication technology (ICT) in education at the beginning of the 21st century. The focus is on how teachers use ICT in their teaching and how students learn in an ICT environment. For this purpose the influence of ICT on teachers’ and students’ beliefs, actions, values and pedagogy were investigated. The theoretical underpinnings of the thesis are derived from four different discourses about the influence of ICT on education. Fox and Twining’s (2006) rationales for ICT use in education provide the context of the questions asked in the thesis, with reference to the more general discussion about the use of ICT in education. The framework of ten Brummelhuis and Kuiper (2008) draws attention to the various driving forces of ICT in relation to the learning processes, and Mishra and Koehler (2006) present an important perspective on the intersection and relationship between technological, pedagogical and content knowledge. Finally and foremost, the framework presented by Webb and Cox (2004) provides a fruitful theoretical base and guides the whole work, in particular as it emphasises the affordances that ICT offers and suggests how the teachers and students make use of it, very importantly on the basis of their knowledge and beliefs or attitudes. The study takes, as a point of departure, the use of ICT in an environment that can be expected to give an exemplary view of what is done at the frontier of ICT use, in a normal school environment. A case study was conducted at one upper secondary school, Menntaskólinn í Kópavogur (MK). At the beginning of the century MK was already a promising ICT school which supported an ICT educational environment. The school was chosen as it had a long history of initiatives in ICT use and the teachers, identified by the school authorities as active ICT users, also had a history of ICT use in their work. Their students were also approached as well as the school authorities. In total ...